Single Molecule Upconversion-Linked Immunosorbent Assay with Extended Dynamic Range for the Sensitive Detection of Diagnostic Biomarkers - Farka, Zdeněk; Mickert, Matthias J; Hlaváček, Antonín; Skládal, Petr; Gorris, Hans H (Analytical chemistry, 2017)
The ability to detect disease markers at the single molecule level promises the ultimate sensitivity in clinical diagnosis. Fluorescence-based single-molecule analysis, however, is limited by matrix interference and can only probe a very small detection volume, which is typically not suitable for real world analytical applications. We have developed a microtiter plate immunoassay for counting single molecules of the cancer marker prostate specific antigen (PSA) using photon-upconversion nanoparticles (UCNPs) as labels that can be detected without background fluorescence. Individual sandwich immunocomplexes consisting of (1) an anti-PSA antibody immobilized to the surface of a microtiter well, (2) PSA, and (3) an anti-PSA antibody-UCNP conjugate were counted under a wide-field epifluorescence microscope equipped with a 980 nm laser excitation source. The single-molecule (digital) upconversion-linked immunosorbent assay (ULISA) reaches a limit of detection of 1.2 pg mL-1 (42 fM) PSA in 25% blood serum, which is about ten times more sensitive than commercial ELISAs, and covers a dynamic range of three orders of magnitude. This upconversion detection mode has the potential to pave the way for a new generation of digital immunoassays.
Keywords: prostatický specifický antigen; Immunosorbents; Nanoparticles; Immunoassay; Prostate-Specific Antigen; Limit of Detection; luminiscence; Luminescence; limita detekce; biologické markery; imunoanalýza; imunosorbenty; Biomarkers; nanočástice